Exploring the microbial landscape of the nasopharynx in children: a systematic review of studies using next generation sequencing - Zimmermann, Petra (Frontiers in Microbiomes, 2023)
Introduction The nasopharynx harbours a diverse and dynamic microbial community, which plays an important role in maintaining the health and homeostasis of the respiratory tract, as well as in immune system development. Understanding factors that influence the composition of the nasopharyngeal microbiome in children and its association with diseases is of particular importance, as children are at a heightened risk for respiratory infections and other adverse health outcomes. Objectives This review systematically summarises studies which investigated the nasopharyngeal microbiome in children, including its dynamics, stability over time, and the influence of intrinsic and extrinsic factors on its composition. Methods MEDLINE was searched using the OVID interface. Original studies which investigated the nasopharyngeal microbiome using next generation sequencing in children were summarised. Results The search identified 736 studies, of which 77 were included. The studies show that the nasopharyngeal microbiome in children is dynamic and influenced by many external factors. A high abundance of Haemophilus, Moraxella, and Streptococcus and a low abundance of Corynebacterium and Dolosigranlum are associated with adverse health outcomes such as respiratory tract infections, wheezing and asthma exacerbations. Factors which have been identified as risk factors for these adverse health outcomes, such as being born by Caesarean section, not being breast-fed, having siblings, day-care attendance, and antibiotic exposure have been shown to be associated with the aforementioned features in the nasopharyngeal microbiome. Conclusion The association between specific nasopharyngeal microbial profiles and adverse health outcomes highlights the potential of the nasopharyngeal microbiome as a marker for identifying children at risk for disease and even more importantly, as an avenue for targeted interventions and preventive strategies.